Peak Troponin I Levels Are Associated with Functional Outcome in Intracerebral Hemorrhage - Gerner, Stefan; Auerbeck, Katrin; Sprügel, Maximilian; Sembill, Jochen; Madzar, Dominik; Gölitz, Philipp; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen; Hölter, Philip (Cerebrovascular Diseases, 2018)
Background: Troponin I is a widely used and reliable marker of myocardial damage and its levels are routinely measured in acute stroke care. So far, the influence of troponin I elevations during hospital stay on functional outcome in patients with atraumatic intracerebral hemorrhage (ICH) is unknown. Methods: Observational single-center study including conservatively treated ICH patients over a 9-year period. Patients were categorized according to peak troponin I level during hospital stay (<= 0.040, 0.041-0.500, > 0.500 ng/mL) and compared regarding baseline and hematoma characteristics. Multivariable analyses were performed to investigate independent associations of troponin levels during hospital stay with functional outcome -assessed using the modified Rankin Scale (mRS; favorable 0-3/unfavorable 4-6) -and mortality after 3 and 12 months. To account for possible con-founding propensity score (PS)-matching (1: 1; caliper 0.1) was performed accounting for imbalances in baseline characteristics to investigate the impact of troponin I values on outcome. Results: Troponin elevations (> 0.040 ng/mL) during hospital stay were observed in 308 out of 745 (41.3%) patients and associated with poorer status on admission (Glasgow Coma Scale/National Institute of Health Stroke Scale). Multivariable analysis revealed troponin I levels during hospital stay to be independently associated with unfavorable outcome after 12 months (risk ratio [95% CI]: 1.030 [1.009-1.051] per increment of 1.0 ng/mL; p = 0.005), but not with mortality. After PS-matching, patients with troponin I elevation (= 0.040 ng/mL) versus those without had a significant higher rate of -unfavorable outcome after 3 and 12 months (mRS 4-6 at 3 months: < 0.04 ng/mL: 159/265 [60.0%] versus = 0.04 ng/mL: 199/266 [74.8%]; p < 0.001; at 12 months: < 0.04 ng/mL: 141/248 [56.9%] versus <= 0.04 ng/mL: 179/251 [71.3%]; p = 0.001). Conclusions: Troponin I elevations during hospital stay occur frequently in ICH patients and are independently associated with functional outcome after 3 and 12 months but not with mortality. (c) 2018 S. Karger AG, Basel
EVALuna2:34936